2019
DOI: 10.2147/imcrj.s217742
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combined Central Retinal Vein And Artery Occlusion In A Patient With Elevated Level Of Factor VIII: A Case Report</p>

Abstract: PurposeTo report a case of unilateral central retinal vein occlusion (CRVO) with central retinal artery occlusion (CRAO) in a patient with elevated Factor VIII.Case presentationA 48-year-old woman presented with a complaint of decreased visual acuity in her left eye that began 6 weeks prior. The patient had diabetes. The best-corrected visual acuity (BCVA) was hand motion, IOP was 34 mmHg, and there was a neovascularization of the iris in the left eye. A complete fundus evaluation including fluorescein angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…(2,3) Arterial occlusion is a rare condition, with an estimated incidence of 8.5 cases per 100,000 inhabitants, usually secondary to fatty embolus from the internal carotid artery, and it presents as sudden and painless visual field loss. (4)(5)(6) The CRVO has an estimated prevalence of 0.4% and its occlusions, (13) but they were not present in this patient. Carotid Doppler ultrasound and echocardiography are important ancillary tests to order and elucidate etiology of the cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…(2,3) Arterial occlusion is a rare condition, with an estimated incidence of 8.5 cases per 100,000 inhabitants, usually secondary to fatty embolus from the internal carotid artery, and it presents as sudden and painless visual field loss. (4)(5)(6) The CRVO has an estimated prevalence of 0.4% and its occlusions, (13) but they were not present in this patient. Carotid Doppler ultrasound and echocardiography are important ancillary tests to order and elucidate etiology of the cases.…”
Section: Discussionmentioning
confidence: 93%
“…(9) Systemic findings found in CRAO combined with CRVO include diabetes, hypertension, dyslipidemia, as well as inflammatory, coagulation and tumoral disorders. (12,13) Recently, high factor VIII indices have been associated with venous thromboembolism in cases of combined venous and arterial In 6-month follow-up of the condition in RE, there was a complete vascular recanalization, with no glaucoma associated, but atrophy of the retinal inner layers on OCT (Figure 5).…”
Section: Case Reportmentioning
confidence: 99%
“…Regarding APS associated with pure ophthalmic manifestations however, there are no current guidelines nor any therapeutic actions suggested other than for preventing subsequent events. Furthermore, systemic anticoagulation, particularly with warfarin, has been linked to increased risk of subsequent retinal vein and arterial occlusion, even at therapeutic dosages [55][56][57].…”
Section: Treatmentmentioning
confidence: 99%
“…88 Whilst reports have been conflicting, a number of studies have demonstrated an association between thrombophilia and the presence of pro-thrombotic markers with retinal vascular occlusions; this includes high homocysteine levels, lupus anticoagulant, factor V Leiden mutation, high anticardiolipin IgM levels, protein C and S deficiency, lipoprotein a, elevated fibrinogen levels and increased plasma viscosity. 87,[89][90][91][92][93][94] Critically ill patients in intensive care are commonly found to develop hemostasis abnormalities and deranged coagulation. 95 Furthermore, patients with severe COVID-19 disease present with significant coagulation abnormalities leading to venous and arterial thromboembolic complications.…”
Section: Retinal Vascular Occlusionsmentioning
confidence: 99%